Adaptive Rationality among Madura Grocery Store Owners: The Role of Experience, Intuition and Social Capital in Sales Strategies - Rifky Faidillah; Wahyu Rahmatullah; Muhammad Fikry (Riset Anak Bangsa, 2026)
Competition between traditional grocery stores and modern retail outlets requires Madura grocery store owners to make appropriate sales decisions despite constraints in capital, information, and business management. This study analyzed how Madura grocery store owners in Paiton District make decisions when determining their sales strategies. A descriptive qualitative approach was employed, involving three owners selected purposively. Data were collected through semi-structured interviews, observation, and documentation and analyzed using an interactive model comprising data condensation, data display, and conclusion drawing and verification. Data credibility was strengthened through source triangulation. The findings show that sales strategies are not developed through formal business planning but evolve from trading experience, observations of community needs, intuition, and conditions in the business environment. Owners retain customers through friendly service, social proximity, product variety, pricing based on operating costs and purchasing power, and inventory adjustments aligned with local consumption patterns. Experience provides the primary basis for interpreting market demand, whereas intuition is used when decisions must be made rapidly. The study concludes that the sustainability of Madura grocery stores depends on owners' capacity to adaptively integrate economic considerations, practical experience, and social capital when responding to retail competition.